Fostering Scientific Literacy in University Students Majoring in Elementary Education Based on Mental State - Edward Harefa; Xiao Huang (Buana Pendidikan, 2023)
Improving the scientific literacy of teacher-training students majoring in elementary education is important in training elementary science education talents in colleges and universities before teaching their prospective students. In this study, we investigated the effectiveness of elementary education teacher-training students' learning the course Fundamentals of Natural Science by developing a mental state questionnaire and a science literacy quiz. The results showed that teacher-training students majoring in elementary education had higher mental states in the course learning process, and their academic achievement was significantly different in terms of background variables such as gender and birth origin. Moreover, there was a significant correlation between mental states and academic achievement. A multidimensional assessment of academic achievement based on mental status will help develop elementary education students' scientific literacy.